Post-partum supplementation of calcium salts of long-chain fatty acids and fibrolytic enzymes on reproductive performance and blood metabolites of lactating Surti buffaloes - J. K. Movaliya et al. (Indian Journal of Dairy Science, 2025)
Twenty-four lactating Surti buffaloes (with an average body weight of 459.21±7.39 kg and parity of 2.58±0.15) that had recently calved were randomly divided into four treatment groups. The first group was the Control (CON) group, which was fed only the basal diet. The second group was fed the exogenous fibrolytic enzymes (EFE) supplement, while the third and fourth groups (BF-1 and BF-2) were fed EFE along with 1% and 2% of bypass fat of total DMI, respectively. Blood biochemical parameters were measured at the start (0 day), middle (75th day), and end (150th day) of the experiment. The results showed that the treatments had no significant effect on the serum levels of glucose, total protein, T3, T4, urea, and lipid profile (including triglycerides, total cholesterol, HDL, LDL, VLDL, and NEFA). Although the onset of post-partum heat was earlier in the group that received bypass fat and enzyme supplements, the difference was not statistically significant. However, animals that received these supplements had a significantly reduced service period and fewer services per conception when compared to the control group. This suggests that adding bypass fat and fibrolytic enzyme supplements to animals' diets can improve their reproductive performance without negatively impacting their blood biochemical indicators.